(untitled) (The Research of Medical Science Review, 2025)
Introduction: ‘Video games have become ever more popular among learners of age 10-15 years old, and so there is concern about their effects, especially on young learners’ cognition. While some papers point to the advantages of attention and working memory updates, there are also papers indicating that they bring different problems, such as addictions and memory deterioration. Objective: To establish the association between video game play and cognitive performance, specifically attention, memory, and the executive functioning of children between the ages of 10 and 15 years through a cross-sectional study. Materials and Method: This cross-sectional study involved 200 children from schools in Karachi and ensured global participation through Google Forms between January and June 2024. The children undertook the Wechsler Intelligence Scale for Children Fifth Edition (WISC-V) and a survey on their gaming audience. Descriptive statistics, correlational analysis, and linear regression analysis tests were run on the data using SSPS version 22. Results: Gamers showed significantly higher attention (p<0.001) and executive functioning (p=0.002) scores but no memory differences (p=0.12). Action games yielded the strongest benefits. Excessive gaming (>3 hours daily) reduced gains. Conclusion: Moderate gaming enhances attention and executive functioning but not memory. Balanced gaming practices are recommended to maximize cognitive benefits while minimizing risks.